Tackling Female Infanticide Social Mobilisation in Dharmapuri, 1997-99 - VENKATESH ATHREYA, SHEELA RANI CHUNKATH (Economic and Political Weekly December 2, 2000, 2000)
The heinous practice of female infanticide (FI) is widespread in several Indian states - even in states which boast of a better record in reducing gender inequality. These include the three southern states, minus Kerala, but also Maharashtra. FI is not merely not dying away, it is emerging as a disturbing new phenomenon. That eradication of this practice is not on the agenda of the central or concerned state governments or even of the major political parties reflects the gender insensitivity in our society and polity. However, in Tamil Nadu over the last four-five years, a serious governmental effort is on to address the issue. Evidence from a set of interventions in Dharmapuri district suggests that with political will, widespread generation of awareness and social mobilisation, a dent can be made in eradicating the evil of FI.